Terrestrial pyrogenic carbon export to fluvial ecosystems: lessons learned from the White Nile watershed of East Africa - Güereña, David T.; Lehmann J; Walter T; Enders A; Neufeldt, Henry; Odiwuor, H.; Biwott, H.; Recha, John W.M.; Shepherd K; Barrios, E.; Wurster C (Wiley, 2015)
Pyrogenic carbon (PyC) is important because of its role in the global organic C (OC) cycle and in modifying soil properties. However, our understanding of PyC movement from terrestrial to fluvial ecosystems is not robust. This study examined (i)whether erosion or subsurface transport wasmore important for PyC export from headwaters, (ii) whether PyC was exported preferentially to total OC (TOC), and (iii) whether themovement of PyC from terrestrial to aquatic ecosystems provides an explanation for the coupling of PyC and non-PyC observed in rivers at a global scale. In the Guineo-Congolian highland forest region of western Kenya, duplicate catchments with sizes of 1–12 ha were equipped with stream gauges in primary forest and adjacent mixed agricultural landscapes that were cleared by fire 10, 16, or 62 years before. Stream water samples were taken weekly throughout 1 year and compared with runoff to assess PyC movement. Additional stream samples were taken fromall major tributaries of theWhite Nile watershed of Lake Victoria. PyC was not found to be preferentially eroded relative to TOC or non-PyC, as topsoil (0–0.15m) PyC concentrations (6.3 ± 0.3% of TOC; means and standard errors) were greater than runoff sediment (1.9 ± 0.4%) and dissolved PyC concentrations (2.0 ± 0.4%, n= 252). In addition, PyC proportions in eroded sediment were lower than and uncorrelated (r2=0.04; P= 0.14) with topsoil PyC. An enrichment of PyC was found with depth in the soil, from 6.3 ± 0.3% of TOC in the topsoil (0–0.15 m) to 12.3 ± 0.3% of TOC at 1–2m. Base flow PyC proportions of TOC correlated well with subsoil PyC (r2=0.57; P<0.05) but not with topsoil PyC (r2=0.18; P>0.05). Similar PyC proportions were found in the studied headwater streams (2.7 ± 0.2%), their downstream inflow into Lake Victoria (3.7%), the other ninemajor rivers into Lake Victoria (4.9 ± 0.8%), and its outflow into the White Nile (1.1%). A strong positive correlation between dissolved PyC and non-PyC (r2 = 0.91; P<0.0001) in the headwater streams reflect relationships previously seen for a range of globally important rivers, and contrasts with a negative relationship for suspended sediments (r2 = 0.5; P<0.0001). The estimated PyC export from the Lake Victoria watershed of 11 Gg yr 1may therefore originate to a large extent from subsoil pathways in dissolved form that appeared to be animportant source of PyC in aquatic environments and may explain the coupling of PyC and non-PyC at a global scale.